An analysis of consumer’ complaint intentions and complaint responses towards unethical advertisements / Hani Zulaikha Zulkifly - Zulkifly, Hani Zulaikha (2016)
This study analyses the link between consumers’ complaint intentions and complaint responses towards unethical advertisements. Specifically, this study explores why the consumers who intend to complain about the unethical advertisements, ended up complaining privately, directly to the advertisers, to the third parties or did not complain at all. In-depth interviews were conducted amongst eighteen highly educated consumers. The findings postulate that the complaint responses are different depending on the sense of responsibility, involvements with the advertised products, experiences regarding the effects of unethical advertisements, the complaint procedures, time constraints, and knowledge on complaint channels as well as rights as the consumers. Fundamentally, this study explains why individuals did not behave according to their intentions.